2020
DOI: 10.1016/j.scitotenv.2020.139658
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19's impact on the atmospheric environment in the Southeast Asia region

Abstract: Impact of lockdown due to COVID-19 on aerosols and pollutants over Southeast Asia • Reduction in Himawari-8 AOD at urban areas is not affected by seasonal biomass burning • Large reductions (~27%-34%) of tropospheric NO 2 over urban agglomerations • Reductions in PM 10 , PM 2.5 , NO 2 , SO 2 , and CO are 26-31%, 23-32%, 63-64%, 9-20%, and 25-31%, respectively, in Malaysia (urban)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
255
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(295 citation statements)
references
References 80 publications
22
255
3
1
Order By: Relevance
“…Myllyvirta and Thieriot (2020) found population-weighted average reductions of 30% for NO 2 and 1% for PM 10 in Austria. Our results are also in line with the observed effect of lockdown measures on air pollution in other parts of the world, as estimated by Petetin et al (2020) , Baldasano (2020) and Kanniah et al (2020) , among others, but different environments and lockdown measures do not permit a quantitative comparison of the reduction effect.…”
Section: Summary and Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Myllyvirta and Thieriot (2020) found population-weighted average reductions of 30% for NO 2 and 1% for PM 10 in Austria. Our results are also in line with the observed effect of lockdown measures on air pollution in other parts of the world, as estimated by Petetin et al (2020) , Baldasano (2020) and Kanniah et al (2020) , among others, but different environments and lockdown measures do not permit a quantitative comparison of the reduction effect.…”
Section: Summary and Discussionsupporting
confidence: 88%
“… Bauwens et al (2020) show that tropospheric NO 2 levels fell by 40% over Chinese cities and by 20–38% in Europe and North America. Kanniah et al (2020) found a drop of around 30% over urban areas in Malaysia. The effect was even stronger for near-surface levels of NO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 pandemic lockdown, several studies around the world have studied its impact on air quality. Ghahremanloo et al [51] reported NO 2 reductions of up to 83% in East Asia, while in Southeast Asia, region reductions were observed in PM 10 (26-31%), PM 2.5 (23-32%), NO 2 (63-64%), SO 2 (9-20%), and CO (25-31%), in urban areas from Malaysia [52]. In India, AOD reductions of up to 50% were perceived in New Delhi [5].…”
Section: Correlation Sars-cov-2 Infections With Meteorological and Aimentioning
confidence: 99%